Fluoro-deoxy glucose positron emission tomography brain as a potent marker for antibody-mediated neurodegeneration in dementia: A case report - Maini, Deepinder Kaur; Handa, Rahul; Arora, Saurabh; Anand, Rajiv; Rehani, Varun (Indian Journal of Case Reports, 2025)
Rapidly progressive dementia (RPD) is a subacute onset progressive disease with cognitive decline which can be associated with vascular, neurodegeneration (prion disease- Creutzfeldt-Jakob disease), inflammatory (immune-mediated or infection), or neoplastic causes. RPD can be fatal with high morbidity and mortality if diagnosis is delayed or misdiagnosed. Our aim is to understand the role and sensitivity of magnetic resonance imaging (MRI) brain versus Fluoro-deoxy glucose positron emission tomography (FDG PET) brain, for the diagnosis of paraneoplastic neurologic syndrome (PNS). We present the case of an 80-year-old female with progressive dementia. MRI brain was suggestive of atrophy in the cerebellum and frontal lobes while FDG PET revealed diffuse hypometabolism in the frontal and temporoparietal region with focal hypermetabolic focus in the left parietal lobe, indicating concomitant neuroinflammation and neurodegeneration. This newer entity named as antibody-mediated neurodegeneration causing dementia can be slowed or reversed to some extent if detected early. However, there is still a lack of consensus on the diagnostic sensitivity of FDG PET Brain in PNS. Our case shows the clinical benefit of FDG PET brain over MRI brain in anti-neuronal antibody-associated dementia to detect neuroinflammatory etiology, a potentially treatable disease.